Cytokine and T cell responses in post-chikungunya viral arthritis: A cross-sectional study. - Aileen Y Chang; Sarah R Tritsch; Carlos Andres Herrera Gomez; Liliana Encinales; Andres Cadena Bonfanti; Wendy Rosales; Evelyn Mendoza-Torres; Samuel Simmens; Richard L Amdur; Christopher N Mores; Paige Fierbaugh; Carlos Alberto Perez Hernandez; et al. (PLoS ONE)
Objective To define the relationship between chronic chikungunya post-viral arthritis disease severity, cytokine response and T cell subsets in order to identify potential targets for therapy. Methods Participants with chikungunya arthritis were recruited from Colombia from 2019-2021. Arthritis disease severity was quantified using the Disease Activity Score-28 and an Arthritis-Flare Questionnaire adapted for chikungunya arthritis. Plasma cytokine concentrations (interleukin (IL)-1β, IL-2, IL-4, IL-6, IL-8, IL-10, IL-12p70, IL-13, interferon-γ and tumor necrosis factor (TNF)) were measured using a Meso Scale Diagnostics assay. Peripheral blood T cell subsets were measured using flow cytometry. Results Among participants with chikungunya arthritis (N = 158), IL-2 levels and frequency of regulatory T cells (Tregs) were low. Increased arthritis disease activity was associated with higher levels of inflammatory cytokines (IL-6, TNF and CRP) and immunoregulatory cytokine IL-10 (p<0.05). Increased arthritis flare activity was associated with higher Treg frequencies (p<0.05) without affecting T effector (Teff) frequencies, Treg/Teff ratios and Treg subsets. Finally, elevated levels of IL-2 were correlated with increased Treg frequency, percent Tregs out of CD4+ T cells, and Treg subsets expressing immunosuppressive markers, while also correlating with an increased percent Teff out of live lymphocytes (p<0.05). Conclusion Chikungunya arthritis is characterized by increased inflammatory cytokines and deficient IL-2 and Treg responses. Greater levels of IL-2 were associated with improved Treg numbers and immunosuppressive markers. Future research may consider targeting these pathways for therapy.